Synthesis, Characterization and Ion-exchange Study of Organo-soluble Copolymer from 8-Quinolinyl Methacrylate and Styrene - A. PATEL, SAMIR; M. PATEL, RAJNI; M. PATEL, PRAVIN (Asian Journal of Chemistry, 2010)
The monomer, 8-quinolinyl methacrylate (8-QMA) was synthesized and characterized by IR and H1 -NMR spectroscopy, high performance liquid chromatography (HPLC) and elemental analysis. The homopolymer poly (8-QMA) and copolymers with styrene in different feed ratio were prepared by free radical polymerization using dimethyl formamide (DMF) as a solvent and 2,2'-azobisisobutyronitrile (AIBN) as an initiator. The resulting polymers were characterized by IR-spectroscopy, UV-visible spectmphotometry, gel permeation chromatography (GPC) and the thermal properties , were measured by TG and DSC. The metal ion uptake capacity of synthesized copolymers was estimated by batch equilibrium method using different metal ion solutions under three different experimental conditions. It was observed that due to the presence of a pendent ester bound quinolinyl group, the copolymers are capable of adsorbing the tested cation from their aqueous solutions.